Evidence of Precambrian sedimentation/magmatism and Cambrian metamorphism in the Bitlis Massif, SE Turkey utilising whole-rock geochemistry and U-Pb LA-ICP-MS zircon dating - Ustaomer, P. Ayda; Ustaomer, Timur; Gerdes, Axel; Robertson, Alastair H. F.; Collins, Alan S. (ELSEVIER, 2012)
The Bitlis Massif is a regional-scale, south-vergent allochthon that was finally emplaced by collision of the Eurasian and Afro-Arabian plates during Miocene time. The Bitlis Massif includes a large outcrop of Precambrian continental crust, the closest counterpart to which is the Arabian-Nubian Shield similar to 1000 km to the south. The Massif is sub-divided into two rock associations: a pre-Middle Devonian high-grade basement and a Middle Devonian-Triassic low-grade cover. The pre-Devonian basement comprises meta-granitic plutons emplaced into high-grade metamorphic rocks, including schist, paragneiss, amphibolite and eclogite. New laser-ablation zircon ages obtained for zircons separated from a meta-granite body and its host paragneiss provide constraints on magmatism, sedimentation and metamorphism. Whole-rock geochemical data indicate that the pluton crystallised from peraluminous I-type melts from an arc-type subduction influenced source. Sm-Nd isotope systematics suggest crustal contamination. Zircon dating yielded a Pb-206/U-238 age of 572 +/- 4.8 Ma, interpreted as the time of crystallisation. Igneous zircons exhibit metamict metamorphic domains dated at 529 Ma (Early Cambrian), interpreted as the time of latest Pan-African metamorphism. Nine detrital zircon grains from host paragneiss yielded Neoproterozoic ages (992-627 Ma). Combined with the crystallisation age data, this suggests that the sedimentary protolith of the paragneiss was deposited from similar to 627 to similar to 572 Ma (Ediacaran). The late Neoproterozoic ages suggest the Bitlis Massif is a peri-Gondwanan terrane with a likely origin in northeast Africa where similar early Neoproterozoic (0.9-1.0 Ga) ages have been reported. (C) 2011 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.
Keywords: Neoproterozoic; Arc magmatism; U-Pb zircon dating; Bitlis Massif; SE Turkey; SOUTHERN MENDERES MASSIF; ARABIAN-NUBIAN SHIELD; OSSA-MORENA ZONE; GEOLOGICAL EVOLUTION; GEODYNAMIC EVOLUTION; CADOMIAN OROGENY; WESTERN TAURIDES; AGE CONSTRAINTS; SANDIKLI AREA; SUTURE ZONE; Geology